IMPLEMENTASI MODEL ASSURE SEBAGAI PENDEKATAN DESAIN PEMBELAJARAN INTERAKTIF DI MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Mulyawan Safwandy Nugraha; Siti Wildan Diniati; Tarsono Tarsono (Raudhah - Proud To Be Professional, 2023)
Learning design is important in determining the success of the learning process so that learning is clear and focused. However, in fact, problems were found that occurred in the learning process, students were less active, lacked motivation to learn, and experienced boredom. Therefore, the aim of this research is to determine the application of the ASSURE model in overcoming these problems as well as its challenges and potential. This research uses a qualitative approach with a descriptive-analytical model. Data collection techniques used observations in class VI at SDN Sawah Lega 01, totalling 42 students, interviews with the Principal, PAI teacher, and two students in class VI and documentation studies. The result is that the use of the ASSURE model in PAI learning is effective in involving students, making students active and not bored. The challenges faced are in terms of student involvement, teachers must always be patient and continue to look for the best way when the RPP and the field experience discrepancies. The potential is that teachers have the skills to make learning plans, the school has openness in receiving evaluations, and there are adequate facilities and infrastructure. In conclusion, the ASSURE learning model has had a positive impact on students in class VI at SDN Sawah Lega 01, Haurdengdek, Cicalengka.